Soil geography - Eni, D.D; Iwara, A.I (Magnum Publishing, 2016)
"Soil geography is a branch of soil science that studies the pattern of distribution of soils on the earth's surface for the purpose of soil-geographic regionalization. There is general and regional soil geography. General soil geography studies the factors that influence soil formation and the most general laws of the geographic distribution of soils and types of soil structure. Regional soil geography is concerned with regionalization and with the description of the soils in individual regions. Soil Geography covers geographic methods to study the distribution of soils in relation to the factors influencing soil formation."--Back cover.